Phase 4: Invisible Moments - Federico Escalante (Oz, 2005)
Within the multitude of the senses lies a deeper understanding of each situation and creating a more meaningful set of mental experiences. Literature has a superb possibility of creating multiple conclusions and experiences based on the individual’s recollection and understanding.